Subfoveal choroidal thickness changes in carotid cavernous fistula following spontaneous resolution. Issue 1 (December 2016) - Rey, Amanda; Castillo, Lorena; Dyrda, Agnieszka; Maseras, Xavier; Jürgens, Ignasi
Abstract Background We report the enhanced depth imaging optical coherence tomography (EDI-OCT) characteristics and variations in a patient with subretinal fluid secondary to a carotid cavernous fistula. Case presentation A 59-year-old man presented with blurred vision in his right eye. Venous congestion of the epiescleral and retinal vessels were observed. EDI-OCT disclosed macular subretinal fluid with an increase of choroidal thickness up to 341 μm. Brain and orbital computerized tomography showed an enlarged right superior ophthalmic vein. Orbital magnetic resonance imaging and angiography disclosed a decrease in blood flow, an indirect sign of carotid cavernous fistula. After a 3 months follow-up, spontaneous closure of the fistula occurred. Both the dilation of the conjunctiva and retinal veins improved. EDI-OCT showed resolution of the subfoveal fluid and a reduction of the subfoveal choroidal thickness to 271 μm after a 3 months follow-up and 168 μm after a 8 months follow-up. Conclusion Serous retinal detachment has been described as a rare complication of carotid cavernous fistula. In our patient, EDI-OCT examinations revealed a thicker choroidal thickness when subretinal fluid was present as compared to that observed in the contralateral eye or after subretinal fluid resolution.